Simulation and Analysis of Malaria Using Multiagent Systems - Costa, Laurence N. da S.; Adamatti, Diana Francisca (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Malaria is a disease that affects hundreds of millions of people globally and causes about 1.2 million deaths every year. Just in Brazil, there is about three hundred thousand cases of malaria per year. It’s a very serious problem of public health in the countries which the disease is endemic. This paper proposes the creation of a computational model of malaria, based on Multiagent Systems (MAS), which covers aspects such as infection, mortality, length of incubation and prevention. The choice to use MAS and Netlogo allowed the creation of a system which has simpler implementation, but highly configurable and, with the public health experts help and successive refinements, it can deliver results more and more reliable.